The Swedish Jews and the Holocaust - Rudberg, Pontus (Routledge, Taylor & Francis Group, 2017)
The first phase (1933-1938) -- The second phase (from November 1938 to the outbreak of the war) -- The third phase (from the outbreak of the war to September 1941) -- The fourth phase (1941-1945) -- The Swedish Jews and the Holocaust